Generating and manipulating transgenic animals using transposable elements - Largaespada David A (BMC, 2003)
Abstract Transposable elements, or transposons, have played a significant role in the history of biological research. They have had a major influence on the structure of genomes during evolution, they can cause mutations, and their study led to the concept of so-called "selfish DNA". In addition, transposons have been manipulated as useful gene transfer vectors. While primarily restricted to use in invertebrates, prokaryotes, and plants, it is now clear that transposon technology and biology are just as relevant to the study of vertebrate species. Multiple transposons now have been shown to be active in vertebrates and they can be used for germline transgenesis, somatic cell transgenesis/gene therapy, and random germline insertional mutagenesis. The sophistication of these applications and the number of active elements are likely to increase over the next several years. This review covers the vertebrate-active retrotransposons and transposons that have been well studied and adapted for use as gene transfer agents. General considerations and predictions about the future utility of transposon technology are discussed.